QUALITATIVE ANALYSIS OF MOBILE PHONE USE IN CLASSROOM ON HIGH SCHOOL STUDENTS' BEHAVIOR - Cheri Khadijah Yustiawan; M.Arifin Ilham; Rafif Mar’ie Muhammad; Ashila Fayyaza Sinaga; Arifin Wahyudi Hasibuan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The development of communication technology, especially mobile phones, has affected various aspects of life, including education. At the high school level, the use of mobile phones in class has become an issue that has positive and negative impacts. On the one hand, mobile phones facilitate access to information and support learning, but on the other hand, they cause distraction, reduce concentration, and affect student discipline. Several studies have shown that uncontrolled mobile phone use has a negative impact on students' academic achievement. However, when used wisely, mobile phones can be an effective learning tool. This study aims to explore the effect of mobile phone use on high school students' concentration and active participation in learning. The conclusion suggests that schools need to implement a balanced policy to control mobile phone use and maximize its benefits in education.